DIGITALIZATION OF PUBLIC ADMINISTRATIONS IN UZBEKISTAN: EXPERIENCE AND EXPECTATIONS. (Marketing Journal, 2025)
In this article, we will review the experience of digitizing public administration and enterprises in Uzbekistan, evaluate its results and development prospects, and analyze the main challenges and issues facing the government of Uzbekistan on this path.
Keywords: digitalization; public administration; information technology; e - government; e -service; digital technology